Unbroken : a World War II story of survival, resilience, and redemption - Hillenbrand, Laura (New York : Random House, 2010)
On a May afternoon in 1943, an Army Air Forces bomber crashed into the Pacific Ocean and disappeared, leaving only a spray of debris and a slick of oil, gasoline, and blood. Then, on the ocean surface, a face appeared--Lt. Louis Zamperini. Captured by the Japanese and driven to the limits of endurance, Zamperini would answer desperation with ingenuity; suffering with hope, resolve, and humor.
Includes bibliographical references (p. [407]-457) and index.
Keywords: Zamperini, Louis, -- 1917-2014.; United States. -- Army Air Forces. -- Bombardment Group, 307th.; World War, 1939-1945 -- Prisoners and prisons, Japanese; Prisoners of war -- United States -- Biography; Prisoners of war -- Japan -- Biography; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Pacific Area; Long-distance runners -- United States -- Biography